2015
DOI: 10.1016/j.sbspro.2015.06.020
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Discourse Analysis of the Electoral Talks of Iranian Presidential Candidates in 2013

Abstract: On Friday, 14 June 2013 one of the most significant events of Iran and the Middle East happened: the presidential election of Iran. The 11th president of Iran started his term on 3rd August 2013. The election was in fact a competition between two main parties: Principlist and Reformist. This paper studied the speeches of the nominees of these two parties: Mohammad Bagher Ghalibaf and Hassan Ruhani. We selected one of their speeches on their election campaigns and incorporated their statements and stances in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The results of the research show that a person's reading ability is based on motivation and seriousness in understanding a reading. Likewise with Ismail (2009), Muslikah (2012), Gowhary (2015), Hayati (2018), andNisya (2020) the results of their research show that reading skills are very Gusnetti, Agustina, Ermanto, M. Zaim IJoLP Open Access Journal: http://ijolp.ppj.unp.ac.id/index.php/ijolp important for someone to master because reading comprehension is one of the keys to success not only in the academic field only, but also in the social field.…”
Section: Introductionmentioning
confidence: 95%
“…The results of the research show that a person's reading ability is based on motivation and seriousness in understanding a reading. Likewise with Ismail (2009), Muslikah (2012), Gowhary (2015), Hayati (2018), andNisya (2020) the results of their research show that reading skills are very Gusnetti, Agustina, Ermanto, M. Zaim IJoLP Open Access Journal: http://ijolp.ppj.unp.ac.id/index.php/ijolp important for someone to master because reading comprehension is one of the keys to success not only in the academic field only, but also in the social field.…”
Section: Introductionmentioning
confidence: 95%
“…This causes a related relationship between social practice and the process of forming discourse. For this reason, the study was done on the context of text production, text consumption, and socio-cultural aspects that influence the formation of discourse (Gowhary et al, 2015;Jalali & Ansaripour, 2014). Fairclough explains that there is a dialectical relationship between social practice and the process of discourse formation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, discourse is shaped by power associated with ideology. Thus, the critical discourse analysis approach formed by Fairclough is called the Dialectical-Relational Approach (DRA) or also known as the social change approach (Eriyanto, 2001;Gowhary et al, 2015;VanWinkle, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the third was introduced by Fairclough (1989) and aimed to investigate important changes happening in our advanced world and their impact on the general population's strategies for communication. Utilizing Fairclough's (1989) relational-dialectic approach, Gowhary, Rahimi, Azizifar, and Jamalinesari (2015) examined the Iranian presidential talks and demonstrated that the targeted candidates were extraordinarily influenced by their diverse political strands, making them take different positions in their political, social, and ideological viewpoints in portrayals, explanations, clarifications, and description of numerous texts within the same topic. Dastpak and Taghinezhad (2015) studied the persuasion strategies in Obama's political speeches demonstrating a comprehensive picture of U.S. society and the need for solidarity.…”
Section: Introductionmentioning
confidence: 99%